2016
DOI: 10.1542/peds.2015-4490
|View full text |Cite
|
Sign up to set email alerts
|

Newborn Resuscitation Training in Resource-Limited Settings: A Systematic Literature Review

Abstract: CONTEXT: Birth asphyxia contributes substantially to neonatal mortality in low-and middleincome countries (LMICs). The effects of training birth attendants in neonatal resuscitation (NR) on mortality are limited by falloff of skills and knowledge over time and transference of learned skills into clinical practice.OBJECTIVE: This review examined acquisition and retention of NR knowledge and skills by birth attendants in LMICs and the effectiveness of interventions to improve them.DATA SOURCES: Medline, Cochrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
69
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(75 citation statements)
references
References 61 publications
5
69
0
1
Order By: Relevance
“…The importance of this should not be underestimated as many studies have shown that booster training is vital in maintaining resuscitation skills over time 14. In a systematic review, Reisman et al 25 showed significantly improved retention of neonatal resuscitation knowledge and skills in health workers who, among other things, practised bag-and-mask skills regularly.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of this should not be underestimated as many studies have shown that booster training is vital in maintaining resuscitation skills over time 14. In a systematic review, Reisman et al 25 showed significantly improved retention of neonatal resuscitation knowledge and skills in health workers who, among other things, practised bag-and-mask skills regularly.…”
Section: Discussionmentioning
confidence: 99%
“…Past assessments of health‐care worker knowledge and skills in newborn care in lower‐middle‐income countries have also identified that many staff perform below competency levels . Barriers in establishing supportive practices following birth, such as with kangaroo mother care, require significant training time and resources, and resuscitation skills can be affected by decrement in knowledge and skills with time, requiring a long‐term approach to quality improvement …”
Section: Discussionmentioning
confidence: 99%
“…The poor achievement of chest rise in all resuscitations suggests that effective ventilation was not reliably accomplished. Along with stimulation, highquality BMV is one of the most important interventions, but several studies reported that learning to provide BMV was more difficult than other aspects of newborn resuscitation for birth attendants [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…In situ simulation and lowdose/high-frequency training have been demonstrated to be effective in high-resource settings [13], and encouraging results have been reported in low-resource settings [14][15][16][17]. Our previous study in a low-resource setting showed improved clinical performance of midwives after participation in an adapted NRP course, while the quality and timing of resuscitations remained below the recommended standards [18].…”
mentioning
confidence: 80%